De la controverse à la conversion : Venise et la défense de la rhétorique dans The Ephemerides of Phialo de Stephen Gosson - Anne Geoffroy-Piscou (Revue LISA)
Controversy was raging in England in the late 1570s and early 1580s as Puritans attacked the evils of the age and above all the stage. Stephen Gosson is well-known for having joined the anti-theatrical polemics in his Schoole of Abuse. However, this article will focus on his less known euphuistic fiction entitled The Ephemerides of Phialo (1579) which he had actually started just before writing his attack on the misuse of art. The fact that Gosson chose to locate his prose fiction in Venice is highly significant and this study argues that the city’s association with vices provides an appropriate, though paradoxical, setting for Gosson’s defence of rhetoric at the expense of fiction. Furthermore, Gosson’s representation of Venice as a “colledge of curtezans” should be viewed against his own attempt to resume his studies at Corpus Christi. Ultimately, if Gosson failed to secure Sir Philip Sidney’s patronage—despite dedicating The Ephemerides to Sidney—he contributed to including and furthering the image of Venice within the field of prose fiction while denouncing the very evils of fiction itself.